Learning in Smart Village Concept Case Study Tanggungan Village Baureno District Bojonegoro Regency - Tjitjik Rahaju,; Tauran,; Badruddin Kurniawan,; M. Noer Falaq,; Melda Fadiyah Hidayat,; Mohammad Bagus Badi', (Technium Social Sciences Journal, 2023)
The development of information and communication technology is widely used in government, one of which is at the village government level. With the provision of authority and large financial rights to the village government, a siskeudes application was developed to facilitate accountability. This study uses a descriptive qualitative research method. The smart village system aims to increase the efficiency of village governance. In its implementation, almost all elements of the smart village have been fulfilled except for one element that has not been achieved, namely the infrastructure element, lack of understanding, potential for fraud, lack of supervision and technical problems that occur in the field. In general, the implementation of this program is good but still needs improvement in several aspects.